Histopathological, histoenzymological, immunohistochemical and immunofluorescence analysis of tissue response to sealing materials after furcation perforation. (5th June 2019) - Silva, R. A. B.; Borges, A. T. N.; Hernandéz‐Gatón, P.; de Queiroz, A. M.; Arzate, H.; Romualdo, P. C.; Nelson‐Filho, P.; Silva, L. A. B.
Abstract: Aim: To evaluate in vivo tissue responses after sealing furcation perforations in dog's teeth with either Biodentine™, mineral trioxide aggregate (MTA) or gutta‐percha, by means of histopathological, histoenzymological, immunohistochemical and immunofluorescence analysis. Methodology: After root canal treatment, perforations were created in the central region of the pulp chamber floor using a round diamond bur and filled with one or other of the materials. The animals were euthanized after 120 days, and the teeth ( n  = 30) were processed for histopathological analysis of new mineralized tissue formation and collagen fibre reinsertion, immunohistochemical analysis of osteopontin (OPN) and alkaline phosphatase (ALP) and immunofluorescence analysis for bone morphogenetic protein (BMP‐2), cementum attachment protein (CAP), bone sialoprotein (BSP), osteocalcin (OCN) and cementum protein1 (CEMP1). Histoenzymology was performed for TRAP activity and osteoclast count. Data were analysed statistically (α   = 0.05) using chi‐square and Kruskal–Wallis tests. Results: Gutta‐percha did not induce mineralized tissue formation. MTA and Biodentine TM formed mineralized tissue in 88% and 92% of specimens, respectively, with no significant difference ( P  > 0.05). Gutta‐percha was associated with scattered collagen fibres parallel to the perforations. Groups treated with MTA or Biodentine TM had partial fibre reinsertion perpendicular to the newly formed mineralized tissue. All materials induced OPN and ALP expression, weakest for gutta‐percha and strongest for MTA ( P  < 0.05). Only MTA induced BMP‐2, BSP, OCN, CAP and CEMP1 expression. Osteoclast counts were similar in all groups ( P  = 0.97). Conclusions: Mineral trioxide aggregate and Biodentine TM were biocompatible, with formation of mineralized tissue and partial reinsertion of collagen fibres. In addition, the participation of several molecules by which calcium silicate‐based materials induce the formation of mineralized tissue were noted, with expression of ALP and OPN mineralization markers, without interference in the number of osteoclasts. Only MTA stimulated the expression of proteins associated with the formation of a cementum‐like mineralized tissue.